2014
DOI: 10.1128/jvi.02141-13
|View full text |Cite
|
Sign up to set email alerts
|

Nonmuscle Myosin Heavy Chain IIA Is a Critical Factor Contributing to the Efficiency of Early Infection of Severe Fever with Thrombocytopenia Syndrome Virus

Abstract: Severe fever with thrombocytopenia syndrome virus (SFTSV) is a novel phlebovirus in the Bunyaviridae family. Most patients infected by SFTSV present with fever and thrombocytopenia, and up to 30% die due to multiple-organ dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
106
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 39 publications
2
106
1
1
Order By: Relevance
“…Previous studies demonstrated that HeLa cells were not susceptible to SFTSVpv and SFTSV infection (5,7). In this study, HeLa cells were weakly susceptible to infection with these viruses ( Fig.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Previous studies demonstrated that HeLa cells were not susceptible to SFTSVpv and SFTSV infection (5,7). In this study, HeLa cells were weakly susceptible to infection with these viruses ( Fig.…”
Section: Discussionmentioning
confidence: 54%
“…Recently, it was reported that a C-type lectin, dendritic cell-specific intercellular adhesion molecule 3-grabbing nonintegrin (DC-SIGN), is an initial binding receptor for SFTSV (5), as was previously reported for other phleboviruses (6). It was also reported that nonmuscle myosin heavy chain IIA is critical for the cellular entry of SFTSV (7). Analysis of the initial steps of SFTSV infection, including identification of the entry receptors and the role of viral GP in membrane fusion, may facilitate the development of entry inhibitors.…”
mentioning
confidence: 82%
“…Ailenin diğer üyeleri gibi negatif zincirli üç RNA segmenti içerir. Büyük segmenti L viral transkripsiyon ve replikasyonda rol oynayan RNA'ya bağımlı RNA polimeraz (RdRP) enzimini kodlar, orta büyüklükteki M segmenti bağı-şıklık ile ilgili olan ve "glikoprotein n" (Gn) ile "glikoprotein c" (Gc)'yi kodlayan bölgedir; diğerlerinden küçük olan S segmenti ise virüsün nükleoproteinleri (Np) ve yapısal olmayan proteinlerini (NSs) kodlar (18) .…”
Section: Trombositopeni Sendromlu Yüksek Ateş Virüsüunclassified
“…Recently, NMHC-IIA was also reported to serve as an entry receptor for severe fever with thrombocytopenia syndrome virus (SFTSV) (30). Like HSV-1 entry, cell surface expression of NMHC-IIA was induced upon SFTSV infection (30). Moreover, NMHC-II activity for cellular protrusions such as filopodia, retraction fibers, and microvilli has been reported to be required for entry of several viruses, including Kaposi's sarcoma-associated herpesvirus (KSHV), papillomavirus, vaccinia virus, and murine leukemia virus (MLV) (31)(32)(33)(34).…”
mentioning
confidence: 99%
“…Cell surface expression of NMHC-IIA appears to be regulated by MLCK-mediated signaling events and to be required for efficient HSV-1 infection, based on the observations that (i) NM-IIA RLC phosphorylation as well as cell surface expression of NMHC-IIA upon HSV-1 entry is inhibited by ML-7, a specific inhibitor of MLCK, and (ii) ML-7 inhibits HSV-1 infection in vitro and in vivo (24). Recently, NMHC-IIA was also reported to serve as an entry receptor for severe fever with thrombocytopenia syndrome virus (SFTSV) (30). Like HSV-1 entry, cell surface expression of NMHC-IIA was induced upon SFTSV infection (30).…”
mentioning
confidence: 99%